OPTIMASI PERENCANAAN PRODUKSI PADA PT X INDUSTRI TEKSTIL MENGGUNAKAN PEMROGRAMAN LINEAR - Alwi Sihab; Rian Padkur Rohman, Muhammad Dhani Al Farizhi, Paduloh (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2025)
Efficient and optimized production planning is essential in the textile industry to increase productivity and reduce production costs. PT X, as one of the textile companies in Indonesia, faces challenges in managing production resources optimally to meet dynamic market demands. This study aims to analyze and optimize production planning at PT X by using linear programming. The linear programming model used integrates various variables such as production capacity, raw materials, labor time, to determine the most efficient production combination. The results of this study show that the application of linear programming can improve production efficiency, minimize costs. Thus, the use of this method can help PT X in planning production more effectively and efficiently